A new Ischnomera of the I. xanthoderes (Mulsant, 1858) complex (Coleoptera: Oedemeridae) from Sicily - Bologna, Marco A.; Poloni, Riccardo; Vázquez, Xavier A. (Zootaxa, 2019)
A new Ischnomera from northern Sicily is described. Besides this species, in the western Mediterranean I. xanthoderes complex were distinct one species from the Iberian peninsula and southern France (I. xanthoderes), and one from northwestern Africa (I. tenietensis). All species are figured and a key to the species is published.